Recent improvements of long-path DOAS measurements: impact on accuracy and stability of short-term and automated long-term observations - Nasse, Jan-Marcus; Eger, Philipp G.; Pöhler, Denis; Schmitt, Stefan; Frieß, Udo; Platt, Ulrich (Atmospheric measurement techniques discussions, 2019)
Abstract: Over the last few decades, differential optical absorption spectroscopy (DOAS) has been used as a common technique to simultaneously measure abundances of a variety of atmospheric trace gases. Exploiting the unique differential absorption cross section of trace-gas molecules, mixing ratios can be derived by measuring the optical density along a defined light path and by applying the Beer–Lambert law. Active long-path (LP-DOAS) instruments can detect trace gases along a light path of a few hundred metres up to 20 km, with sensitivities for mixing ratios down to ppbv and pptv levels, depending on the trace-gas species. To achieve high measurement accuracy and low detection limits, it is crucial to reduce instrumental artefacts that lead to systematic structures in the residual spectra of the analysis. Spectral residual structures can be introduced by most components of a LP-DOAS measurement system, namely by the light source, in the transmission of the measurement signal between the system components or at the level of spectrometer and detector. This article focuses on recent improvements by the first application of a new type of light source and consequent changes to the optical setup to improve measurement accuracy. Most state-of-the-art LP-DOAS instruments are based on fibre optics and use xenon arc lamps or light-emitting diodes (LEDs) as light sources. Here we present the application of a laser-driven light source (LDLS), which significantly improves the measurement quality compared to conventional light sources. In addition, the lifetime of LDLS is about an order of magnitude higher than of typical Xe arc lamps. The small and very stable plasma discharge spot of the LDLS allows the application of a modified fibre configuration. This enables a better light coupling with higher light throughput, higher transmission homogeneity, and a better suppression of light from disturbing wavelength regions. Furthermore, the mode-mixing properties of the optical fibre are enhanced by an improved mechanical treatment. The combined effects lead to spectral residual structures in the range of 5−10×10−5 root mean square (rms; in units of optical density). This represents a reduction of detection limits of typical trace-gas species by a factor of 3–4 compared to previous setups. High temporal stability and reduced operational complexity of this new setup allow the operation of low-maintenance, automated LP-DOAS systems, as demonstrated here by more than 2 years of continuous observations in Antarctica.